2015
DOI: 10.1097/apo.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Severe Visual Impairment and Blindness

Abstract: Consistent with other studies, there is a high rate of blinding disease, which may be prevented, treated, or ameliorated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Additionally, the number of children blind due to lenticular (17 vs 11 students) and retinal causes (13 vs 11 students) was not signi cantly different between 2009 and 2021, respectively. Compared to neighbouring countries, the distribution of causes of eye disease in Cambodian children appears to be similar to those reported in Laos (11) and provincial towns in the Philippines (12) while there is a greater proportion of corneal causes of blindness than that seen in Malaysia (13), Mongolia (14) or Sri Lanka (15).…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, the number of children blind due to lenticular (17 vs 11 students) and retinal causes (13 vs 11 students) was not signi cantly different between 2009 and 2021, respectively. Compared to neighbouring countries, the distribution of causes of eye disease in Cambodian children appears to be similar to those reported in Laos (11) and provincial towns in the Philippines (12) while there is a greater proportion of corneal causes of blindness than that seen in Malaysia (13), Mongolia (14) or Sri Lanka (15).…”
Section: Discussionsupporting
confidence: 67%
“…We found the highest rate of causative mutations in Bhutan (two of five probands). The audit also reported no cases of measles/ rubella induced vision loss in the Bhutanese school children (Farmer et al, 2015). It remains to be determined how many of the probands with no detected mutations in this panel of genes have genetic forms of cataract and how many may be accounted for by environmental causes.…”
Section: Discussionmentioning
confidence: 97%
“…Children under 16 years of age attending blind schools in Bhutan (Farmer et al, 2015), Cambodia (Sia et al, 2010), and Sri Lanka (Gao et al, 2011) underwent an ocular examination and review of records as part of audits of the causes of childhood blindness in each community as described previously (Farmer et al, 2015;Gao et al, 2011;Sia et al, 2010). While all children were examined at the time of recruitment, it was not possible to access historical medical records to determine age of onset, or to interview the family for a detailed history.…”
Section: Participant Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other recent childhood blindness studies performed in Asia have also found whole globe anomalies to be the main cause of blindness including India (25%),[ 9 ] Lao (30.4%),[ 10 ] and Bhutan (20%). [ 10 ] Corneal opacities, however, still remains the most common site of abnormality in sub-Saharan Africa and areas of extreme deprivation. [ 2 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%